OPTIMIZING ORGANIZATIONAL RESILIENCE: A LITERATURE REVIEW ON THE ROLE OF HUMAN RESOURCE MANAGEMENT - Dessy Mita Mariana Malau; Muammar Khaddafi; Irawati; Edy Purnomo; M. Oscar; Chikmah Dona Sunita; Rayessandi; Erni Lubis; Syamsudin; Katherine (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study endeavors to explore the intricate connection between Human Resource Management (HRM) practices and Organizational Resilience, with a specific emphasis on dimensions such as leadership, innovation, employee performance, and system satisfaction. Employing a literature review methodology, a comprehensive understanding framework was constructed by examining insights from various prominent studies available in Scopus, ScienceDirect, and ResearchGate journals. The outcomes underscore the pivotal role of HRM in confronting unparalleled challenges, especially during crises like the COVID-19 pandemic. Notably, it was discovered that the quality of systems, information, and services significantly influences user satisfaction within e-learning systems. Furthermore, the characteristics of boards, including board size, the proportion of independent commissioners, and board meeting frequency, exhibit an impact on CSR disclosure in the mining industry. The findings also illuminate the intricate nature of digital HRM transformation, emphasizing the necessity for a holistic approach that encompasses process reengineering, competency development, and organizational culture change. Practical implications emanating from the research involve refining marketing and service strategies based on factors that influence customer satisfaction. In the context of bolstering global competitiveness, the study highlights the pivotal role of knowledge management, emphasizing the imperative to concentrate on knowledge management strategies amidst intensifying global competition. Consequently, this research contributes profound insights, theoretical advancements, and invaluable practical recommendations for prospective research endeavors and HRM practitioners.